Validation and predicting total body water in people with spinal cord injury using bioelectrical impedance analysis. Issue 1 (2nd January 2022) - Aldobali, Mahmood; Pal, Kirti; Chhabra, Harvinder Singh
Abstract: The purpose of this study was validation of predictive equations for total body water (TBW) in people with spinal cord injury (SCI) compared to healthy subjects (HS) using bioelectrical impedance analysis (BIA). The method used was sample size of 104 (52 each group) with 41 males in SCI, 39 in HS, 11 females in SCI, and 13 in HS. A T-test was applied to statistical analysis between groups. The results showed significant differences between groups of gender, with p-value < P 0.0013, the difference (4.6115), with a 95%CI (1.8480 to 7.3750), and SE (1.3932). The SCI group noted a difference within BIA and formula calculations. In conclusion, we found the current equations inaccurate in SCI society and recommended BIA as non-invasive, speedy, portable, accessible, and cost-effective.